The Wiley handbook of developmental psychology in practice : implementation and impact - Durkin, Kevin; Schaffer, H. Rudolph (Chichester, West Sussex : Wiley-Blackwell, 2016)
'Serves as an invaluable resource for developmental psychologists, practitioners working in the field of child development, and policymakers working on issues affecting children and families'--
Child Care and Child DevelopmentResearch to Policy; Research to Public Awareness; Reflections from Seven Developmentalists on Working at the Nexus; Strategies for Success; References; 8 Teenage Childbearing in the United States; Teenage Mothers' Parenting Skills; Teenage Mothers' Educational Attainment; Factors That Influence Teenage Mothers' Well-being; Interventions for Teenage Mothers; Obstacles Faced by Programs Serving Teenage Mothers; Primary Prevention of Teenage Pregnancy and Childbearing; Practical Reflections: What Helps and Where Next?; Conclusion; References
Machine generated contents note: Notes on Contributors PART ONE: FAMILY PROCESSES AND CHILD REARING PRACTICES 1. Editorial Introduction: On giving developmental psychology away Kevin Durkin and H. Rudolph Schaffer 2. The role of popular literature in influencing parents' behavior Penelope Leach 3. Opportunities and obstacles in giving away research on marital conflict and children E. Mark Cummings, W. Brad Faircloth, Patricia M. Mitchell, Kathleen McCoy and Alice C. Schermerhorn 4. Implementing a preventive parenting program with families of young children: Challenges and solutions Angela D. Moreland & Jean E. Dumas 5. Parenting information and advice and the mass media Matthew R Sanders and Rachel Calam 6. Children of lesbian and gay parents: Reflections on the research-policy interface Charlotte J. Patterson and Rachel H. Farr. 7. Child care at the nexus of practice, policy, and research Christina Hardway and Kathleen McCartney 8. Teenage childbearing in the U.S.: Do our programs and policies reflect our knowledge base? Anne Martin and Jeanne Brooks-Gunn PART TWO: EDUCATIONAL ASPECTS 9. The trials and tribulations of changing how reading is taught in schools: Synthetic phonics and the educational backlash Rhona S Johnston and Joyce E Watson 10. Giving away early mathematics: Big Math for Little Kids encounters the complex world of early education Herbert P. Ginsburg and Barbrina B. Ertle 11. Avoiding the psychologist's fallacy in using what we have learned about children's moral development to address moral education Larry Nucci and Marcy J. Hochberg 12. Toward a truly democratic civics education Charles C. Helwig and Shaogang Yang 13. Research and practice in the study of school bullying Peter K. Smith 14. Promoting pedestrian skill development in young children: Implementation of a national community-centred behavioral training scheme James A. Thomson 15. Researcher-practitioner partnerships in the development of intervention to reduce prejudice among children Lyndsey Cameron and Adam Rutland PART THREE: CLINICAL ASPECTS 16. What do we know and why does it matter? The dissemination of evidence-based interventions for child maltreatment Dante Cicchetti, Sheree L. Toth, Wendy J. Nilsen, and Jody Todd Manly 17. Language impairment and adolescent outcomes Gina Conti-Ramsden and Kevin Durkin 18. Translating models of adolescent problem behavior into effective intervention: Trials, tribulations and future directions Thomas J. Dishion and Miwa Yasui 19. Giving away knowledge about children's mental health: Challenges and opportunities Janice Cooper & Jane Knitzer Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Developmental psychology; Psychology, Applied; PSYCHOLOGY / Developmental / General; Developmental psychology; Psychology, Applied; Electronic books; Electronic books